RETRACTED ARTICLE: The Relations Between Blood Pressure and Handgrip Strength in Children - Gentiana Beqa Ahmeti; Besnik Morina; Georgi Georgiev; Seryozha Gontarev (OVS LLC, 2023)
Background. Studies, previously completed, announce that the handgrip strength as a measurement for assessing muscle fitness is associated with cardiovascular risk factors. Yet, the relation of handgrip strength to the blood pressure in children is inconsistent. Therefore, we conducted the present research aiming to establish the relation of the handgrip strength to the blood pressure in Macedonian children from the Skopje region. Materials and methods.  The research was conducted on a sample of 1076 children (534 boys and 542 girls), whereby the following characteristics were measured: blood pressure, handgrip strength, weight, height, body fat percentage, waist circumference and the body mass index (BMI) was calculated. General linear models were used to examine the association between handgrip strength and the outcome variables. Results. After the adjustment of age, gender, BMI, body fat percentage and waist circumference, the handgrip strength was statistically significantly positively associated to both systolic (P<0.0001) and diastolic (P=0.02) blood pressure. There was a growing trend of the systolic blood pressure as the handgrip strength increased from the lower quartile to the upper quartile with 3,7 mm Hg difference between the upper and lower quartile (P for trend = 0.03). In this research, it was not established a statistically significant trend of the diastolic blood pressure as the hand grip strength increases from the lower quartile to the upper quartile (P for trend=0.09). Conclusions. The muscle fitness has a positive correlation with the blood pressure in the respondents. The implications and the basic mechanisms of these results require further research studies.